The Concept of Legal Certainty in The Final and Binding Decision of The Election Manager Honorary Council (DKPP) - Nisaq, Rista Choirun; Haruni, Catur Wido; Anoraga, Surya (Audito Comparative Law Journal (ACLJ), 2024)
The final and binding phrase on the DKPP decision in the provisions of Article 458 paragraph (13) of the Election Law was submitted for judicial review through the Constitutional Court decision Number RI 32/PUU-XIX/2021. In the provisions of Article 458 paragraph (13), the phrase final and binding means that the DKPP's decision can’t be submitted for legal effort. However, from the case of Evi Novida Eka Ginting, the Election Organizer Ethics Council (DKPP) decision can be submitted for legal effort. This has implications for the legal certainty of the final and binding phrase in the provisions of Article 458 paragraph (13). This research aims to analyze the final and binding decisions of the Election Organizer Ethics Council in terms of the Constitutional Court Decision Number.32/PUU-XIX/2021 and Law Number 7 of 2017 concerning Elections and to analyze the Election Organizer Ethics Council decisions. which is final and binding in terms of the aspect of legal certainty. The research method used is normative juridical. Based on the results of the research and discussion, First, viewed from the Constitutional Court decision no. 32/PUU-XIX/2021 the phrase "final and binding" in Article 458 paragraph (13) can be an object in the Administrative Court. What can be submitted is a legal effort, a lawsuit to the Administrative Court (PTUN) to cancel the Presidential Decree. Reviewed according to Law No.7 of 2017 concerning General Elections, Article 458 paragraph (13), the Election Organizer Ethics Council (DKPP) decision is final and binding, this means that the decision cannot be made to legal effort and directly can be held. Second, according to the principle of legal certainty, final and binding phrases cause legal uncertainty. Because the phrase is final and binding on the DKPP decision, it is interpreted that the Election Organizer Ethics Council (DKPP) decision can’t be made due to legal effort and must be held. So the final phrase in Article 458 paragraph (13) should be removed cause the meaning has multiple interpretations.